2021
DOI: 10.1002/app.51697
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing technology and dynamic mechanical investigation of moisture‐resistant Luffa cylindrica‐reinforced epoxy composites

Abstract: Natural fiber (NF)‐reinforced thermosetting composites exhibit excellent properties but, due to the usually hygroscopic nature of the fibers, these composites may suffer from the effects of moisture absorption. Luffa cylindrica is a NF, potentially useful in the manufacture of composite materials, but it is highly hygroscopic. A technology is developed for the fabrication of moisture‐resistant L. cylindrica‐reinforced epoxy composites and the various parameters that affect the process are investigated using lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Luffa cylindrica chopped fibers were treated with 1% acetic acid in acetone, as we have previously described because we found that this treatment achieves the best performance. (Acetone serves as the solvent because this way fibers are not exposed to water which would dramatically increase their volume and lead to decreased properties) 50,51 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Luffa cylindrica chopped fibers were treated with 1% acetic acid in acetone, as we have previously described because we found that this treatment achieves the best performance. (Acetone serves as the solvent because this way fibers are not exposed to water which would dramatically increase their volume and lead to decreased properties) 50,51 …”
Section: Methodsmentioning
confidence: 99%
“…(Acetone serves as the solvent because this way fibers are not exposed to water which would dramatically increase their volume and lead to decreased properties). 50,51 Cotton flocks were partially acetylated (5% wt/wt acetyl groups) by thermal treatment with acetic acid and subsequent addition of acetic anhydride in the presence of perchloric acid (catalyst).…”
Section: Chemical Treatmentmentioning
confidence: 99%